From the Judaism of Jesus to the Christianity of Paul - Lipovsky, Igor P. (American Academy Press, 2022)
"The misconception has taken root in our world that the Christian religion was created by Jesus and his disciples. In fact, the true creators of Christianity were the Apostle Paul and his followers. It was they who wrote almost all the New Testament writings, although they had never seen or heard Christ. However, the true gospel of Jesus was much closer to Pharisaic Judaism than to Pauline Christianity. The disciples of Jesus-the apostles Peter, John and James-preached the teachings of the Son of Man, but their ideological opponent, the Apostle Paul, emphasized something else: the resurrection of the Son of God, which corresponded to the mythology of the pagans. In the second century CE, copyists, themselves former pagans, changed the original texts of New Testament writings to sanctify Paul's ideas with the authority of Jesus and to depict Christ as being in opposition to the Jews. To do this, they made numerous anti-Jewish and anti-Judaic additions to the New Testament. Moreover, they shifted the blame for the crucifixion of Christ from the Romans to the Jews. This blatant falsification of the legacy of Jesus laid the foundation for hostility to the people of Christ"--